Issues of Defining Administrative and Tort Relations as an Object of Legal Research - O. V. Panasiuk (Bulletin of Kharkiv National University of Internal Affairs)
The concept of administrative and tort relations, their social nature, features (properties, characteristics), specific features as a type of administrative and legal relations, structure (objects, subjects and content) and types of administrative and tort relations have been characterized. The grounds for the origin, change and termination of administrative and tort relations, their separation from other similar relations have been highlighted.